Molecular dynamics comparison of E. coli WrbA apoprotein and holoprotein - Reha, David; Harish, Balasubramanian; Sinha, Dhiraj; Kukacka, Zdenek; McSally, James; Ettrichova, Olga; Novak, Petr; Carey, Jannette; Ettrich, Rüdiger (Journal of molecular modeling, 2014)
WrbA is a novel multimeric flavodoxin-like protein of unknown function. A recent high-resolution X-ray crystal structure of E. coli WrbA holoprotein revealed a methionine sulfoxide residue with full occupancy in the FMN-binding site, a finding that was confirmed by mass spectrometry. In an effort to evaluate whether methionine sulfoxide may have a role in WrbA function, the present analyses were undertaken using molecular dynamics simulations in combination with further mass spectrometry of the protein. Methionine sulfoxide formation upon reconstitution of purified apoWrbA with oxidized FMN is fast as judged by kinetic mass spectrometry, being complete in ∼5 h and resulting in complete conversion at the active-site methionine with minor extents of conversion at heterogeneous second sites. Analysis of methionine oxidation states during purification of holoWrbA from bacterial cells reveals that methionine is not oxidized prior to reconstitution, indicating that methionine sulfoxide is unlikely to be relevant to the function of WrbA in vivo. Although the simulation results, the first reported for WrbA, led to no hypotheses about the role of methionine sulfoxide that could be tested experimentally, they elucidated the origins of the two major differences between apo- and holoWrbA crystal structures, an alteration of inter-subunit distance and a rotational shift within the tetrameric assembly.
Keywords: stabilita proteinů; kinetika; methionin; flavinmononukleotid; proteiny z Escherichia coli; Protein Binding; represorové proteiny; Apoproteins; apoproteiny; Molecular Dynamics Simulation; Repressor Proteins; Oxidation-Reduction; Protein Stability; Protein Conformation; vztahy mezi strukturou a aktivitou; Binding Sites; vazba proteinů; Kinetics; Escherichia coli Proteins; simulace molekulární dynamiky; Methionine; oxidace-redukce; Flavin Mononucleotide; hmotnostní spektrometrie s elektrosprejovou ionizací; Structure-Activity Relationship; vazebná místa; Spectrometry, Mass, Electrospray Ionization; konformace proteinů